ANALISIS SROI (SOCIAL RETURN ON INVESTMENT) DALAM MENGUKUR KEBERHASILAN PROGRAM CSR MIKROHYDRO OLEH PT. PJB UP PAITON DI DESA ANDUNGBIRU, KABUPATEN PROBOLINGGO - Astuti, Veronica Sri (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2020)
This study aims to determine the impact / benefits of the CSR Mikrohydro program by PT. PJB UP Paiton in Andungbiru Village, Probolinggo Regency. This can be seen by using the Social Return On Investment (SROI) analysis. Andungbiru Village is a village that is located very remote and is a mountainous area, where the electricity infrastructure is from very minimal even almost unusable. CSR Mikrohydro by PT. PJB UP Paiton helps the people of Andungbiru Village by reactivating the PLTMH (Micro Hydro Power Plant) which once existed during the Dutch colonial era. SROI analysis shows that CSR Mikrohydro by PT. PJB UP Paiton in Andungbiru Village has succeeded in providing benefits and empowering the Andungbiru Village community economically and socially, as well as maintaining environmental sustainability. Keywords: Social Return On Investment; CSR